A practical topological insulator saturable absorber for mode-locked fiber laser - Yan, Peiguang (Sci Rep, 2015)
A novel saturable absorber (SA) was fabricated by coating the topological insulator (TI) film on microfiber using pulsed laser deposition (PLD) method. The TISA device had an insertion loss of ~1.25 dB, a saturable intensity of 26.7 MW/cm(2), a modulation depth of ~5.7%, and a nonsaturable loss of 20.5%. Upon employing this SA device, we established a passively mode-locked EDFL and achieved nearly free-chirped soliton pulse with 286 fs of pulse duration and >73 dB of signal to noise ratio (SNR). This result clearly evidences that the PLD is an effective scheme for practical SA device fabrication.